Prevalence and risk factor of Anemia among Hemodialysis patient: Prevalensi dan faktor risiko anemia pada pasien hemodialisis - Ali Jabbar Abd Al-Husayn (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Anemia is a common and clinically significant complication among patients undergoing hemodialysis, contributing to increased morbidity and complex clinical management in chronic kidney disease. Specific Background: Patients with end-stage renal disease receiving maintenance hemodialysis frequently experience reduced hemoglobin levels related to impaired erythropoietin production, iron deficiency, and comorbid conditions. Knowledge Gap: Despite extensive international evidence, limited localized data are available regarding the prevalence and associated factors of anemia among hemodialysis patients in the studied setting. Aims: This study aimed to determine the prevalence of anemia and identify related demographic and clinical characteristics among patients undergoing hemodialysis. Results: The findings demonstrated a high proportion of anemia among hemodialysis patients, with variations observed according to age, gender, and selected clinical parameters. Laboratory indicators and treatment-related variables were associated with the occurrence and severity of reduced hemoglobin levels. Novelty: This study provides updated contextual evidence on anemia distribution within a defined hemodialysis population, contributing locally derived clinical data to the existing body of nephrology research. Implications: The results underscore the need for structured anemia monitoring, optimized management strategies, and continuous evaluation of hematological parameters in dialysis centers to support improved patient care and clinical decision-making. Keywords: Anemia, Hemodialysis, Chronic Kidney Disease, Hemoglobin Level, Prevalence Key Findings Highlights: A substantial proportion of dialysis recipients presented with reduced hemoglobin values. Demographic and clinical characteristics were linked to variations in blood parameters. Routine hematological assessment remains essential in long-term renal replacement therapy.